Lack of glucuronidation products of trans‐resveratrol in plasma and urine of cats. Issue 2 (8th June 2016) - Burnett, K.; Puschner, B.; Ramsey, J. J.; Lin, Y.; Wei, A.; Fascetti, A. J.
Summary: Resveratrol has generated interest in cats due to reported health benefits. Cats have low activity of β ‐glucuronidase, and we hypothesized they could not form two common resveratrol metabolites, resveratrol‐3‐O‐glucuronide and resveratrol‐4′‐O‐glucuronide. Resveratrol, 3 mg/cat/day, was given orally to intact male ( n  =   5) and female cats ( n  =   5) for 4 weeks. A control group (8 intact males) was used for comparison. Plasma and urine were collected weekly and analysed using high‐pressure liquid chromatography coupled with tandem mass spectrometry. Resveratrol and resveratrol‐3‐O‐sulphate, but no glucuronide metabolites, were detected in plasma and urine. Median (range 10–90th percentile) plasma resveratrol for control and treatment groups was 0.46 ng/ml (0.02–1.74 ng/ml) and 0.96 ng/ml (0.65–3.21 ng/ml). Median (range) plasma resveratrol‐3‐O‐sulphate for control and treatment groups was 6.32 ng/ml (2.55–10.29 ng/ml) and 11.45 ng/ml (1.47–53.29 ng/ml). Plasma resveratrol differed from control in week 4, while plasma resveratrol‐3‐O‐sulphate was different in all weeks (p < 0.05). Median (range) urine resveratrol for control and treatment groups was 0.28 ng/ml (0.05–1.59 ng/ml) and 19.98 ng/ml (8.44–87.54 ng/ml). Median (range) urine resveratrol‐3‐O‐sulphate for control and treatment groups was 26.71 ng/ml (10.50–75.58 ng/ml) and 108.69 ng/ml (11.83–231.05 ng/ml). All time points for urine resveratrol and resveratrol‐3‐O‐sulphate were significantly different from control (p < 0.05), except for weeks 1, 3 and 4 for resveratrol. The results support our hypothesis that cats are unlikely able to glucuronidate resveratrol, most likely due to a reduction in the activity of β ‐glucuronidase.